COVID-19 and suburban public transport in the conditions of the Czech Republic - Fridrisek, Petr; Janos, Vit (Transportation research interdisciplinary perspectives, 2022)
This article focuses on possible approaches to safe regional public transport during the COVID-19 pandemic. The purposes of the research are examination the conditions for ensuring safe transport and the impact on the planning of transport services. The result is an assessment of the operation of regional public transport, consisting of the possibility of maintaining safe distances in public transport. Authors work on suburban transport cases in selected regions of the Czech Republic (Prague and Moravian-Silesian Region). Census devices in public transport, periodical transport surveys, Google mobility reports and data on fare sales from regional transport were used as data sources. Emphasis is placed on a safe distance between commuters, this condition leads to lower occupancy of the vehicle while maintaining the capacity of the vehicles. The value of this new occupancy is determined for selected vehicles and the coefficient that represents the maximum occupancy level to ensure safe transport is established. The capacity of the connections is examined in the period before and during the COVID-19 pandemic. Compared to the period before COVID-19, the daily variation of passengers is expected to change significantly, leading to different occupancy rates during the day.
Keywords: Integrated transport systems; Timetable design; COVID-19 pandemic; Vehicle capacity; Travel demand; Passenger transport